2002
DOI: 10.1074/jbc.m202485200
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Signaling Pathways on the Activation of ERK in B Cells

Abstract: The B cell receptor (BCR) initiates three major signaling pathways: the Ras pathway, which leads to extracellular signal-regulated kinase (ERK) activation; the phospholipase C-␥ pathway, which causes calcium mobilization; and the phosphoinositide 3-kinase (PI 3-kinase) pathway. These combine to induce different biological responses depending on the context of the BCR signal. Both the Ras and PI 3-kinase pathways are important for B cell development and activation. Several model systems show evidence of cross-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
69
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 56 publications
13
69
0
Order By: Relevance
“…Further, inhibition of PI3K with LY294002 before addition of anti-Ig eliminated BCR-induced ERK phosphorylation, as reported (17). However, the situation was very different for B cells previously treated with IL-4.…”
Section: Bcr-induced Erk Phosphorylation Becomes Substantially Pi3k Isupporting
confidence: 65%
See 1 more Smart Citation
“…Further, inhibition of PI3K with LY294002 before addition of anti-Ig eliminated BCR-induced ERK phosphorylation, as reported (17). However, the situation was very different for B cells previously treated with IL-4.…”
Section: Bcr-induced Erk Phosphorylation Becomes Substantially Pi3k Isupporting
confidence: 65%
“…Thus, Bam32 and Carma1 appear to channel BCR-induced intracellular signaling toward distinct pathways (11). However, interconnections between these pathways certainly exist, and it has been shown that ERK activation is dependent on molecules such as PI3K and/or PKC that are key mediators of BCR-triggered NF-B induction (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…This result contrasts with our observations in normal splenic B cells treated with wortmannin in which a requirement for PI-3K is clearly established in BCR-initiated MEK1/2-p42/44ERK phosphorylation. We also observed that LY294004 blocks p42/44ERK phosphorylation following BCR cross-linking, in agreement with a recent report by Jacob et al (57). The molecular basis underlying this discrepancy is currently unknown; however, because all mammalian class I, II, and III PI-3K members show sensitivity to wortmannin and LY294004, it is plausible that BCR-dependent MEK1/ 2-p42/44ERK activation requires PI-3K members other than class I A (58).…”
Section: Discussionsupporting
confidence: 91%
“…PI3K has also been shown to mediate BCR-induced activation of Erk (43). To determine whether this pathway contributes to the down-regulation of FOXO1 mRNA expression, B cells were treated with the Erk inhibitor U0126 before incubation with antiIgM.…”
Section: Resultsmentioning
confidence: 99%